The content of heavy metals in atmospheric deposition in the Pasvik State Nature Reserve vicinity - Ershov V. V.; Isaeva L. G.; Polikarpova N. V. (Vestnik MGTU, 2019)
The dynamics of the heavy metals composition in the atmospheric deposition of pine and birch biogeocenoses near the Pasvik Reserve has been estimated taking into account the influence of air pollution. The objects of study are two monitoring plots located in Betuletum herbosum and Pinetum fruticuloso-hylocomiosum westward the combine "Pechenganikel" (Murmansk region) being a powerful source of sulfur dioxide and heavy metal emissions. The studied period of observation on atmospheric precipitation in the form of snow is 5 years (2009–2013), in the form of rain – 3 years (2010–2012). The plots have been equipped with 8 snow collectors (6 – under the forest canopy, 2 – in the open area), in the form of rain – 23 rain collectors (20 – under the forest canopy and 3 in the open area). Snow and rainwater have being sampled every four weeks. The composition of heavy metals (Cu, Ni, Pb, Cd, Cr, Co) is determined by atomic absorption spectrophotometry. In pine and birch biogeocenoses, significant inter-biogeocenotic variability in the composition of atmospheric precipitation in the form of snow and rain has been revealed. The excess of critical loads in atmospheric deposition of copper, as well as the excess of the maximum permissible concentrations (MPS) for this metal in both types of forest, in the sediments passed through the canopy and in open areas have been revealed. For other metals, the situation looks more stable, in particular exceeding the MPS in fishery of the nickel content in atmospheric deposition has not been identified.